Data accessibility is not sufficient for making replication studies a matter of course - Denis Huschka; Gert G. Wagner (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2012)
Cooperation between researchers, research funders and peerreviewed journals is a key approach - otherwise we will continue to hear merry-go-round rationals why science is still unscientific in the 21st century and nobody's to blame: the researchers as individuals cannot bring about change. They are subject to the incentive systems of their disciplines, which are, in turn, intertwined with the economic interests of the respective publishers. This should not go unchallenged by the academic elite.
Keywords: 330; Wirtschaftsforschung; Sozialforschung; Statistische Daten